Validated repeatability of patient-reported outcome measures following primary total hip replacement: a mode of delivery comparison study with randomized sequencing. (2nd November 2018) - Carpenter, Charlotte V E; Blackburn, Julia; Jackson, John; Blom, Ashley W; Sayers, Adrian; Whitehouse, Michael R
Abstract : Background and purpose — Patient-reported outcome measures (PROMs) are used to understand better the outcomes after total hip replacement (THR). These are administered in different settings using a variety of methods. We investigated whether the mode of delivery of commonly used PROMs affects the reported scores, 1 year after THR. Patients and methods — A prospective test–retest mode comparison study with randomized sequence was done in 66 patients who had undergone primary THR. PROMs were administered by 4 modes: self-administration, face-to-face interview, telephone interview, and postal questionnaire. PROMs included: Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), Oxford Hip Score (OHS), EQ5D-3L (EQ5D), and Self-Administered Patient Satisfaction Scale (SAPS). Linear regression was used to estimate relationships between the mean scores for PROMs by mode. Individual paired differences by mode were calculated, relationships between modes were identified, and results adjusted by time delay and participant age. Results — There was no statistically significant difference between the mean PROM scores recorded for each mode of delivery for each score. Statistically significant differences in the individual paired differences were detected between modes for the WOMAC stiffness subscale, OHS, EQ5D, and SAPS. OHS difference in individual paired means between face-to-face and telephone interview exceeded the minimal clinically important difference. Interpretation — PROMs mode of administration can affect the recorded results. Modes should not be mixed and may not be comparable between studies. It should not be assumed that different modes will obtain the same results and where not already established this should be checked by researchers before use.